PENGARUH PEMAKAIAN BAHAN BAKAR BENSIN PREMIUM DAN PERTAMAX TERHADAP TORSI, DAYA EFEKTIF DAN SFCe PADA MOTOR BENSIN EMPAT LANGKAH EMPAT SILINDER - Nuarsa, I Made (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2011)
Fuel quality had a major effect on improvement of the engine performance. One of the reason is the engine performance to get off is detonation occurs in the combustion chamber. To support this effort is by using high octane fuel as Pertamax. By using those fuel, it is expected to economize the fuel consumption and reduces air pollution level. There by the improvement of the engine performance is expected to be happening.  This research was done to analyse the effect of premium and pertamax consumption in terms of torque, effective power and specific fuel consumption effective (SFCe) on Daihatsu Feroza engine 1589 cc. The instrument for measuring the torque of engine were trommel and brake power system by using brake material that adopts brake prony system.  The experiment was done at wide open throttle (WOT) at fourth transmission at 1600 rpm, 2100 rpm, 2600 rpm, 3100 rpm, and 3600 rpm.  The experiment result was gained maximum of torque, effective power and specific fuel consumption effective (SFCe) to premium gasoline RON 88 at 3600 rpm severally is 12,92 Kg.m, 64,93 PS and 0,10 L/PS.jam and to pertamax gasoline RON 92 severally is 13,52 Kg.m, 67,97 PS and 0,09 L/PS.jam. Average increasing of torque and effective power equal to 6,52% and 6,79%. While the average degradation of spesific fuel consumption effective (SFCe) equal to 16,18%.